The Effect of Authoritative Parenting and Self-Esteem on Prosocial Behavior in Adolescents in Palopo City - Dirham, Izza Fadhlinah; Izzaty, Rita Eka; nurmiati, Nurmiati (International Journal Labs, 2024)
This research is motivated by the phenomenon of low prosocial behavior among high school teenagers in Palopo City. Authoritative parenting by parents and self-esteem are supporting factors for adolescents to increase prosocial behavior. Therefore, this study aims to prove the influence of authoritative parenting and self-esteem on prosocial behavior in high school teenagers in Palopo City. This research employed quantitative research with an ex-post facto type of research with a sample of 335 teenagers. The data collection technique used an accidental sampling technique with research instruments in the form of psychological scales, namely the prosocial behavior scale, authoritative parenting scale, and self-esteem scale. The validity test used the results of factor loading, and the reliability test used Cronbach's Alpha, with a reliability coefficient value for the prosocial behavior scale = 0.910, the self- esteem parenting scale = 0.885, and the self-esteem scale = 0.890. Data were analyzed using multiple regression analysis techniques. The study's results show that authoritative parenting and self-esteem influence prosocial behavior in adolescents (p=0.000). Therefore, it can be concluded that authoritative research and self-esteem influence prosocial behavior in adolescents. The regression line equation is 14.204 + 0.326 X1 + 0.539 X2. The effective contribution of authoritative parenting and self-esteem to prosocial behavior was 44.8%, consisting of authoritative parenting at 17.2% and self-esteem at 27.6%.